Improving the antimicrobial activity of old antibacterial drug mafenide: Schiff bases and their bioactivity targeting resistant pathogens - Krátký, Martin; Konečná, Klára; Šimková, Adéla; Janďourek, Ondřej; Maixnerová, Jana; Stolaříková, Jiřina; Vejsová, Marcela; Voxová, Barbora; Trejtnar, František; Vinšová, Jarmila (Future medicinal chemistry, 2023)
Background: Increasing rates of acquired resistance have justified the critical need for novel antimicrobial drugs. One viable concept is the modification of known drugs. Methods & results: 21 mafenide-based compounds were prepared via condensation reactions and screened for antimicrobial efficacy, which demonstrated promising activity against both Gram-positive and Gram-negative pathogens, pathogenic fungi and mycobacterial strains (minimum inhibitory concentrations from 3.91 μM). Importantly, they retained activity against a panel of superbugs (methicillin- and vancomycin-resistant staphylococci, enterococci, multidrug-resistant Mycobacterium tuberculosis) without any cross-resistance. Unlike mafenide, most of its imines were bactericidal. Toxicity to HepG2 cells was also investigated. Conclusion: Schiff bases were significantly more active than the parent drug, with iodinated salicylidene and 5-nitrofuran/thiophene-methylidene scaffolds being preferred in identifying the most promising drug candidates.
Keywords: Schiff Bases; drug resistance; mafenide; Anti-Bacterial Agents; imine; antiinfekční látky; Mycobacterium tuberculosis; mafenid; Anti-Infective Agents; antifungal activity; Microbial Sensitivity Tests; cytotoxicity; antibacterial activity; Mafenide; Schiffovy báze; enterococci; antibakteriální látky; staphylococci; mikrobiální testy citlivosti; antimycobacterial activity; Schiff bases